Reflexivity and reciprocity to maintain trusting relationships in organisational coaching: a practice framework - Amy Stabler; Joanne James (International Journal of Evidence Based Coaching and Mentoring, 2023)
This paper advances understanding of coaching practice for maintaining trust in organisational coaching relationships. Drawing on a co-produced autoethnographical method, the study illustrates how coaches experience challenges to relational trust and issues of system trust over time. We show how reflexivity allows coaches to consider how the context affects their relationships and offer a practice model for organisational coaches to support cycles of reflexivity and reciprocity for maintaining trust.